Cystoseira myrica: from beach-cast seaweed to fucoidan with antioxidant and anticoagulant capacity - Dhahri, Manel (Frontiers in Marine Science, 2023)
This study highlights the potential of the brown algae Cystoseira myrica, collected from raw beach seaweed wastes, as a reliable source of bioactive fucoidan. Fucoidans are natural bioactive sulfated polysaccharides that are gaining popularity worldwide due to their diverse biochemical composition, attractive physical properties, and functional pharmacological activities. The aim of this work is to valorize the beach-Accumulated brown algae C. myrica by fucoidan extraction and to investigate its anticoagulant and antioxidant activity. Fucoidan was extracted using several steps of papain digestion followed by cetyltrimethylammonium bromide (CTAB) precipitation and calcium chloride treatment to avoid the coextraction of other polysaccharides. Structural features of the extracted fucoidan were investigated by Fourier transform infrared spectroscopy (FT-IR), solid-state nuclear magnetic resonance (NMR) and high-resolution mass spectroscopy. Agarose gel electrophoresis was used to confirm the purity of the isolated fucoidan from C. myrica. Anticoagulant properties were studied in vitro by activated partial thromboplastin time (aPTT) and prothrombin time (PT) assays. Furthermore, the antioxidant activity was investigated by 2,2’-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and Fe chelating ability. Our results indicate that the approach used was effective in extracting fucoidan with a yield of 3.07%, a high amount of sulfate (27.79%), and fucose was found to be the major monosaccharide component. The extracted fucoidan showed an interesting anticoagulant activity. It prolonged aPTT significantly at a concentration of 10 µg/ml and prolonged PT at high doses. This demonstrated that fucoidan from C. myrica may affect intrinsic pathways while having little impact on the extrinsic mechanism of coagulation. However, the extracted fucoidan significantly exhibited an interesting antioxidant capacity as shown by the higher ABTS radical scavenging activity and Ferrous ion-chelating effect. The current findings suggest that fucoidan isolated from C. myrica has unique structural, antioxidant and anticoagulant properties and offers innovative therapeutic possibilities.